The quality of reporting of primary test accuracy studies in obstetrics and gynaecology: application of the STARD criteria - Khan Khalid S; Zamora Javier; Morris R Katie; Selman Tara J (BMC, 2011)
Abstract Background In obstetrics and gynaecology there has been a rapid growth in the development of new tests and primary studies of their accuracy. It is imperative that such studies are reported with transparency allowing the detection of any potential bias that may invalidate the results. The objective of this study was to determine the quality of reporting in diagnostic test accuracy studies in obstetrics and gynaecology using the Standards for Reporting of Diagnostic Accuracy - STARD checklist. Methods The included studies of ten systematic reviews were assessed for compliance with each of the reporting criteria. Using appropriate statistical tests we investigated whether there was an improvement in reporting quality since the introduction of the STARD checklist, whether a correlation existed between study sample size, country of origin of study and reporting quality. Results A total of 300 studies were included (195 for obstetrics, 105 for gynaecology). The overall reporting quality of included studies to the STARD criteria was poor. Obstetric studies reported adequately > 50% of the time for 62.1% (18/29) of the items while gynaecologic studies did the same 51.7% (15/29). There was a greater mean compliance with STARD criteria in the included obstetric studies than the gynaecological (p < 0.0001). There was a positive correlation, in both obstetrics (p < 0.0001) and gynaecology (p = 0.0123), between study sample size and reporting quality. No correlation between geographical area of publication and compliance with the reporting criteria could be demonstrated. Conclusions The reporting quality of papers in obstetrics and gynaecology is improving. This may be due to initiatives such as the STARD checklist as well as historical progress in awareness among authors of the need to accurately report studies. There is however considerable scope for further improvement.